Samatya Kapıağası Yakup Ağa Hamamı restorasyon projesi - Yeşilkaynak, Meltem (Fen Bilimleri Enstitüsü, 1991)
İstanbul'da, tarihi eserlerin yoğun olduğu Samatya semtindeki Sulumanastır ' da yer alan "Kapıağası Yakup Ağa" Hamamı bir çifte hamamdır. Kadınlar ve Erkekler bölümlerinin paralel ve simetrik olarak ortak bir duvar boyunca düzenlendiği bu hamamın ardında yine ortak bir külhan ve odun deposu yer almaktadır. XVI. yüzyılın ilk yarısında Kapıağası Yakup Ağa tarafından Mimarbaşı Koca Sinan'a yaptırılan bu hamam özgün işlevini ve biçimini kaybetmiş ve son halini XX. yüzyıl başlarında almıştır. Hamam konusu, Tez 'in birinci bölümünde vurgulanan çalışma amacının ışığında, toplam yedi ana başlık altında ele alınmıştır. Bunlardan ikincisi "Türk Hamamı"nın tanımı ve tarihçesi hakkındaki genel bilgileri içermektedir. * Ayrıca gelenekselleşen Türk Hamam mimarisinin bölümleri, işlevleri ve günümüze ulaşan örneklere dayanılarak yapılan gruplama çalışmaları da bu bölüm içerisinde belirlenerek, -eklerde incelenmiştir. Üçüncü bölüm yapının araştırılmasında kullanılan yöntemleri dördüncü bölüm ise hamamın günümüze ulaşan halinin tanımlanmasını içermektedir. Çevre ölçeğindeki tanımlamada hamamın çevre yapılarla ilişkisi ve ulaşımı anlatılmaktadır. Yapı ölçeğindeki tanımlama ise, yapının günümüze ulaşan özgün bölümlerinin strüktür ve malzeme açısından incelenmesini ve yapıya eklenen bölümlerin niteliklerini içermektedir. Beşinci bölümde, günümüze ulaşan Sinan Hamamları incelenerek, karşılaştırmalı bir çalışmayla restitüsyona hazırlık oluşturulmaktadır. Altıncı bölüm daha önceki bölüme dayanarak hamamın restitüsyonu konusundaki düşünceleri içermektedir. Yedinci ve son bölümde ise hamamın yapıya ve yöreye uygun bir işlevle, turistik amaçlı bir sosyal merkez olarak kullanımı için restorasyon önerisi geliştirilmekte, bu işleve uygun kullanım için gerekli müdahaleler önerilmektedir.

The "Kapıağası Yakup Ağa" Bath is a double bath si tuated in the Sulumanastir area in Samatya, Istanbul, whe re there are nuTEToushis tori cal monuments. The bath is compo sed of two symmetrical parts; one for men and the other for women. Behind. the building a commonly used boiler room (külhan) and a cellar for the storage Df wood take place. This bath is built by the Master Architect Sinan for Yakup Ağa, an Ottoman Chief of Gate (Kapıağası), in the middle of XVI. th. century. It has lost its function and shape and took its latest form in the beginning of XX th. century. In this thesis, the Traditional Baths and particulary the "Kapıağası Yakup Ağa Bath" are studied under seven main titles especially pointed out in the first chapter. The second chapter covers general information about descripti on and history of the Turkish baths. Their parts, functi ons and the group studies based on the examples of the tra ditional Turkish bath architecture that has survived until today are also studied in this chapter. The Baths which are as old as the human history, we re formad according the religious beliefs and traditional effects in the ancient times. They take a very special place in the Islamic religion in which body cleaning is very important. Since the ancient times, open thermal baths built around hot water springs were called "Ilıca" and the cohered ones were called "Kaplıca", where the bath chambers were sometimes called "Hamam" as well, but the Turks prefered generally to use this name for the baths with boilers. The Seldjuk Turks coming from the Middle Asia built simple buildings for body care and cleaning required by the religion. In the Anatolian-Turkish Baths of the Ottoman period, the pre-Ottoman Anatolian-Turkish architectural style has been generally observed. Such an architectural style originated from the Roman baths was so much improved by the Seldjuks and especially the Ottomans that in the -XVI- end it was called "The Turkish Bath". Bath building ac tivities starting just after the foundation of the Otto mans, increased after the conquer of Istanbul. Thirty two baths were built during Fatih Sultan Mehmet. One of the reasons of building these baths is that they are profitable and make an income for some benefit societies and another reason is chracting more, attendants to the mosques. Most baths were established as foundations of health. The "Kapıağası Yakup Ağa Bath" is classified as pa rallel and symmetrical bath according to the location of its sections for men and women and is grouped under four iwaned and four sudatoriumed plan in the arms of the cross according to the location of its caldaria. Third chapter of the thesis covers the types of methods for examining this building. First steps of the research consists of the documentation of measured areas with photographs. Besides this study based mainly on me asuring and observations, informations have been obtained from the local people who have been around the building for many years. The fourth chapter of the thesis covers the histori cal background and description of the "Kapıağası Yakup Ağa Bath". The bath is assumed to be completed in 1547 and the protector of this bath is "Kapıağası Yakup Ağa"ujha was Chief of the Gate at the Palace. The bath has been dest royed by various natural events and fire, and it is pos sible to state that the apodyterium side "of the bath could be built in the beginning of the XX th. century. The bath was active in its last state until 1925, but lost its customers because of its inadequately heating system and then was closed. The bath was used as a cupper workshop in 1963 and then became a sand paper workshop. Today, its women's caldarium serves as a pin workshop into which a door is opened from the west iwan. The bath is located in north-south direction in Samatya side of the Fatih region. The building is surro unded by roads around its three sides, the Sulumanastir Chapel in north and the Georgios Chapel in south-west. The communication to the Ağa Bath is obtained with Samatya Street and Kocamustafapaşa train Station. Other buildings were added afterwards at the west and south sides of the bath which is surrounded with the other high residences. -xvii- Behind the apodyteria, tepideria and caldaria loca ted from south to north along a wall separating the tuıo sections for men and women, the boiler room and the wood cellar were located in north direction. Both of these sections were built symmetrically, but apodyteria and the entrances were designed in the west of the women's section and in the south of the men's section. Today, the apodyte ria are so different from their previous situation with the south side drawn back and narrowed and both of the doors to the apodyteria are cancelled. The women's apodyterium which is used as stocksroom today is not in a good condition. The mezzanine and the ceiling which are not original, are almost damaged. Also the ground of this place is not original because it was approximately raised D,BO m. when the shops were built un der the apodyteria. Dn the west wall there are the origi nal door of the women's section and two windows; one at the first floor and the other at the second. On the north wall there is a door which is opened to the tepidarium. Today this door is blocked because there is a difference of level between the apodyterium and tepidarium. At both side of the door there are two rectangle niches. There is no niche on the east wall. But there is a door which is opened to the men's apodyterium. This place is full of planks therefore there is no entrance and it is im possible to measure and to examine the architectural properties of the men's apodyterium. Behind the apodyteria, the tepideria of the bath are located. The women's tepidarium has two parts which are separated with a shouldered arch and covered by two similar domes. On the each wall of the tepidarium there are one or two niches and on the north wall there is a door which is opened to the women's caldarium. Dn the domes there are small openings which have starry or hexa gonal forms. The men's tepidarium has similar architectural properties. But only the toilet section is bigger than the other and on the domes there are circular openings. The women's caldarium has four iwaned and four su- datoriumed plan in the arms of the cross into which a do or is opened from the west iwan and a window from the north-west sudatorium. The south iwan was blocked with the wall and combined to the south-east sudatorium. -XVlll- The men's caldarium has similar properties into which a door is opened from the south-east sudatorium and a window from the east iwan. There are no original floor material nor original bath accessories found in the bath. The dome and crossvault design are used in the ceilings of the tepidarium sections and in the caldarium; domes are used in sudatoria and in central locations. All the ceilings are constructed with bricks. Also the vaulted, ceiling of the wood cellar is unique. In the fifth chapter, other baths built by Sinan are compared with the Ağa Bath and information about the pe riod of this bath has been tried tobe obtained, also pre parations for its restitution has been made. İn the sixth chapter of the thesis, data obtained of result of the examination of the bath constructions, the plan and cross-section of the "Kapıağası Yakup Ağa Bath" achieved by H.Glück and other baths constructed by Sinan are chosen as examples for restitution of the subject construction. In conclusion it was decided that the apodyteria were squares with dimensions as 13.50x13.50 m. and retruding lighting ceilings used to cover the above said construction units. The original construction type of the ceilings they still unknown. By ta it is also does not ex floor in th at the firs at the firs level at th there were the door on king into consideration the above information, assumed that the original south wall face, which ist anymore, could have three windows at the top e men's section, two at both sides of the door t floor, and only three windows at the top floor t floor, and only three windows at the top floor e women's section. It is also possible that two windows at the top floor level and one near the east wall face of the apodyterium. The last seventh chapter include a proposal for the restoration of the "Kapıağası Yakup Ağa Bath", the refunc- tionning of the building as a touristic social center which is suitable for the area. This function is suitable also for the continuation of the original plan of the building. The necessary interventions for the restoration and refu- npltionning of the bath are studied in this chapter itself are improved and and necessary steps suitable for such function are presented. As it is known minimum changes must be made to the traditional construction according to the modern restora tion principles. Also there must be no damage given to the historical characteristics of the construction. -xixr- According this principles, the south wall face is planned to be reconstructed with modern materials. The ceiling of the apodyteria must also be reconstructed by using modern materials, but it mill be restored according to its historical characteristcs. The bath mill have shopping area-display hall-res taurant chain of functions. The mezzanines mill be built at the apodyteria which is suitable for the functions as cafeteria and restaurant. The tepideria and the caldaria will be redesigned as shopping area. The water storage tanks are planned to be changed into stocksroom of the shops. The wood cellar will become a snack bar. This construction will be restored according to the scientific methods in the way to be delivered to the coming generations.
The Kapıağası Yakup Ağa Bath
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1992
Keywords: Hamamlar; Kapıağası Yakup Ağa Hamamı; Osmanlı mimarisi; Restitüsyon; Restorasyon; Baths; Kapıağası Yakup Ağa Bath; Ottoman architecture; Restitution; Restoration